Evaluation of schistocyte analysis by a novel automated digital cell morphology application. (28th April 2015) - Hervent, A.‐S.; Godefroid, M.; Cauwelier, B.; Billiet, J.; Emmerechts, J.
Summary: Introduction: TheCellaVision Advanced Red Blood Cell (RBC) Software Application is a new software for advanced morphological analysis of RBC, which automatically performs a preliminary characterization and grouping of RBC into 21 morphological categories, including schistocytes. Upon automated classification, the software offers the possibility of reclassification of RBC by the operator. The aim of this study was to evaluate the schistocyte analysis by theCellaVision Advanced RBC Application. Methods: Schistocyte counts were evaluated comparing the automated count on aCellaVision DM96, both before and after reclassification, with the reference manual microscopic method according to the ICSH criteria. Thirty‐six samples of hospitalized patients and 40 samples of controls were analyzed. Results: Within‐run, between‐run and between‐observer coefficients of variation were lower when counted with theCellaVision compared to the manual microscopic count. The very high sensitivity but rather poor specificity implicates the need for reclassification by the operator, following automated analysis. After reclassification, method comparison studies revealed good agreement with the manual microscopic method, with however slightly higher values of schistocytes for the automated analysis. Conclusion: TheCellaVision Advanced RBC Software Application provides a sensitive and reproducible measurement of schistocytes in peripheral blood, but still requires manual revision. Furthermore, it is an easy‐to‐use software and an excellent teaching tool that might contribute to standardization in the investigation of schistocyte‐related conditions.